2019
DOI: 10.1002/ana.25453
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic patterns across core features in dementia with lewy bodies

Abstract: Objective: To identify brain regions whose metabolic impairment contributes to dementia with Lewy bodies (DLB) clinical core features expression and to assess the influence of severity of global cognitive impairment on the DLB hypometabolic pattern. Methods: Brain fluorodeoxyglucose positron emission tomography and information on core features were available in 171 patients belonging to the imaging repository of the European DLB Consortium. Principal component analysis was applied to identify brain regions rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 52 publications
11
55
0
Order By: Relevance
“…This may be explained by various potentially confounding circumstances. Previous studies have suggested that CIS may be influenced by the severity of cognitive impairment [11,30], however, in line with a previous study [15], we did not find a relationship between CIS and MMSE. The implementation of the visual CIS scale in a routine practice is potentially valuable considering that visual features including cingulate hypometabolism seemed to be underreported and missed on the clinical interpretation of FDG-PET scans of patients with DLB [13].…”
Section: Discussionsupporting
confidence: 86%
“…This may be explained by various potentially confounding circumstances. Previous studies have suggested that CIS may be influenced by the severity of cognitive impairment [11,30], however, in line with a previous study [15], we did not find a relationship between CIS and MMSE. The implementation of the visual CIS scale in a routine practice is potentially valuable considering that visual features including cingulate hypometabolism seemed to be underreported and missed on the clinical interpretation of FDG-PET scans of patients with DLB [13].…”
Section: Discussionsupporting
confidence: 86%
“…Subjects presenting with a normal 18 F-FDG-PET scan or an anterior pattern of hypo-metabolism were considered not to be eligible, while all subjects presented with a posterior pattern of hypo-metabolism felt to be possibly affected with AD or DLB. Details on the 18 F-FDG-PET acquisition were reported elsewhere [11]. To be included in the study, subjects needed to present clearly positive or negative 123 I-FP-CIT-SPECT scan (i.e., evidence of nigrostriatal degeneration for all DLB subjects and for none of the AD subjects based on normative data [12]) performed no later than 6 months after the first access to our centre and to have a clinical follow-up of at least 3 years after the 123 I-FP-CIT-SPECT scan confirming the baseline clinical diagnosis.…”
Section: Dlb and Ad Patientsmentioning
confidence: 99%
“…Putaminal 123 I-FP-CIT SPECT SBR values were 1.300 ± 0.410 and 1.260 ± 0.310 for the left and right putamen in the DLB group and 3.300 ± 0.890 and 3.000 ± 0.610 for the AD group. As per protocol, all DLB subjects and none of the AD subjects presented with 123 I-FP-CIT SPECT SBR values suggestive of NP degeneration based on multicentre normative data [11]. Focusing on the DLB group, there was a significant inverse correlation between 123 I-FP-CIT SPECT putamen SBR values and NP FA values (left, r = -0.670, p = 0.003; right, r = -0.720, p = 0.001; Fig.…”
Section: Correlation Between Np Diffusion Metrics and 123 I-fp-cit Spmentioning
confidence: 99%
“…A recent multi-center 18 F-FDG PET study explored regional correlates for the core symptoms in DLB. 46…”
Section: Diagnostic Clinical Correlates and Predictive Aspect Of mentioning
confidence: 99%